2017
DOI: 10.3389/fimmu.2017.00799
|View full text |Cite
|
Sign up to set email alerts
|

Ras Signaling Inhibitors Attenuate Disease in Adjuvant-Induced Arthritis via Targeting Pathogenic Antigen-Specific Th17-Type Cells

Abstract: The Ras family of GTPases plays an important role in signaling nodes downstream to T cell receptor and CD28 activation, potentially lowering the threshold for T-cell receptor activation by autoantigens. Somatic mutation in NRAS or KRAS may cause a rare autoimmune disorder coupled with abnormal expansion of lymphocytes. T cells from rheumatoid arthritis (RA) patients show excessive activation of Ras/MEK/ERK pathway. The small molecule farnesylthiosalicylic acid (FTS) interferes with the interaction between Ras … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 65 publications
(65 reference statements)
1
22
0
Order By: Relevance
“…In a murine lung cancer model where the oncogenic K‐Ras G12D is expressed at the lung epithelium, accumulation of Th17 cells in the lung tumors was observed . The Ras‐GTPase inhibitor FTS suppressed the differentiation of Th17 cells and the expression of Th17‐associated IL‐17 and IL‐22 . These studies, together with the current one, suggest that Ras signaling might be critical to the development of Th17 cells and the Th17/Treg cell imbalance.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In a murine lung cancer model where the oncogenic K‐Ras G12D is expressed at the lung epithelium, accumulation of Th17 cells in the lung tumors was observed . The Ras‐GTPase inhibitor FTS suppressed the differentiation of Th17 cells and the expression of Th17‐associated IL‐17 and IL‐22 . These studies, together with the current one, suggest that Ras signaling might be critical to the development of Th17 cells and the Th17/Treg cell imbalance.…”
Section: Discussionsupporting
confidence: 70%
“…Ras‐GTPases are key switches that act downstream of the CD3/CD28 signaling and have critical roles in many cellular processes, such as mobilization, differentiation, proliferation and apoptosis . Excessive Ras signaling was shown to associate with excessive Th17 responses in autoimmune diseases . Therefore, we examined the expression of Ras in CD4 + T cells from COPD‐PH patients and controls.…”
Section: Resultsmentioning
confidence: 99%
“…The abundance of Tregs and TH17 cells has been contested in recent publications, but the consensus is that both of these cell types are decreased in LS but with an overall increase in interferon expression (all interferon subtypes). Overexpression of the KRAS signaling pathway has been shown to be critical to the development of Th17 cells and the Th17/Treg cell imbalance (45). The KRAS pathway is thought to induce the IRF7 signaling that leads to increased gene expression and induction of key proteins involved in expression and secretion of interferon gene expression inducing the conversion of CD4+-naïve T to Treg cells by upregulating genes that characterize Tregs, including FOXP3 (46)(47)(48).…”
Section: Pediatric Ls Vs Healthy Control Skin: Inflammation and Fibrosismentioning
confidence: 99%
“…Previous studies demonstrated the activation of Ras/ MEK/ERK in disease models of cerebral ischemia, oxidative stress, and neurodegenerative disease [48][49][50]. Ras/MEK/ ERK has been identified as a novel signaling molecule modulating inflammatory response in the arthritis of animal models [51]. A recent study showed that macrophages CCR1 activation promoted the release of TNF-α and IL-1β via activating Ras/MEK/ERK [19].…”
Section: Discussionmentioning
confidence: 99%